Pengembangan Bahan Ajar Digital Berbasis STEM untuk Meningkatkan Kemandirian Belajar - Dwi Oktaviani Ogara; Hersan Hersan (Sosio-Didaktika: Social Science Education Journal, 2023)
This study aims to: 1) describe the stages of developing STEM-based digital modules; 2) describe student responses to STEM-based digital modules; 3) describe the effectiveness of STEM-based digital modules; and 4) describe the effect of STEM-based digital modules on increasing learning independence. This research is tdevelopment of R&D and experimental research using quantitative data analysis. Research procedure used is a 4-D development model developed by Thiagaraja, Semmel, and Semmel, there are four stages, define, design, develop and disseminate. Obtained data during the development of digital teaching materials will be analyzed by researchers with qualitative and quantitative analysis stages. This qualitative analysis was obtained from data collecting observations, interviews, and questionnaires. Quantitative analysis is intended to describe the quality of teaching materials developed based on the assessment of expert validators. Based on the results of the validation STEM-based Digital Module experts developed in the appropriate category, the student's response to the practicality of the STEM-based Digital Module is in the feasible category, based on the gain score test there are increase in independence, and based on the results of the paired samples test there  are an effect of using the Digital Module on learning independence. Thus, it can be concluded that the STEM-based Digital Module is effectively used to increase learning independence.